The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s002320001028
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Opening GABA A Channels in CA1 Pyramidal Neurones of Rat Hippocampus

Abstract: Spontaneous, single channel, chloride currents were recorded in 48% of cell-attached patches on neurones in the CA1 region of rat hippocampal slices. In some patches, there was more than 1 channel active. They showed outward rectification: both channel conductance and open probability were greater at depolarized than at hyperpolarized potentials. Channels activated by gamma-aminobutyric acid (GABA) in silent patches on the same neurones had similar conductance and outward rectification. The spontaneous current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…Thus, GABA A receptors containing the ␤ 1 subunit may be inhibited by loreclezole or stay unaffected by it. Spontaneously opening GABA A receptors are present in hippocampal neurons (Macdonald et al, 1989;Birnir et al, 2000). It is possible that spontaneously opening GABA A receptors participate in the tonic current described in this article.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, GABA A receptors containing the ␤ 1 subunit may be inhibited by loreclezole or stay unaffected by it. Spontaneously opening GABA A receptors are present in hippocampal neurons (Macdonald et al, 1989;Birnir et al, 2000). It is possible that spontaneously opening GABA A receptors participate in the tonic current described in this article.…”
Section: Discussionmentioning
confidence: 82%
“…Statistical significance compared with the density of current inhibited by picrotoxin for each GABA A receptor type was determined using a one-way ANOVA with post hoc Tukey test: ‫,ءء‬ p Ͻ 0.01 and ‫,ءءء‬ p Ͻ 0.001. side-out patch recordings from pituitary intermediate lobe cells (Taleb et al, 1987) and in cell-attached patch recordings from hippocampal pyramidal neurons (Birnir et al, 2000) and hypothalamic neurons (Jones et al, 2006). We found that spontaneous channel activity in outside-out patches excised from pyramidal neurons were independent of GABA, persisted for prolonged time periods after patch excision, were resistant to gabazine, and were abolished by picrotoxin.…”
Section: (Described Under Materials and Methods)mentioning
confidence: 82%
“…8A below) into a set of differential equations and solved them numerically. Because in the absence of agonist receptors can spontaneously open at very low probability (25)(26)(27), for simulation convenience it was assumed as the initial condition, i.e. at t ϭ 0 no bound or open receptors were present.…”
Section: Methodsmentioning
confidence: 99%